PERBANDINGAN EFEKTIFITAS TERAPI SLOW STROKE BACK MASSAGE DAN FOOT MASSAGE TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DI DESA MEDAN ESTATE - Nita Vebriani Halawa; Lam Murni Sagala (JOURNAL SAINS STUDENT RESEARCH, 2026)
Background: According to the WHO (2016), the elderly are defined as individuals aged 60 years and older. Among the many health conditions affecting the elderly, hypertension is responsible for the deaths of 17.9 million people worldwide each year; this figure accounts for over 31% of all deaths and is also one of the most common health issues affecting the elderly today. Hypertension is a condition characterized by an increase in systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg; at least two blood pressure measurements under different conditions are required to determine the presence or absence of hypertension. Research Objective: To determine the comparative effectiveness of slow stroke back massage (SSBM) and foot massage in reducing blood pressure among the elderly in Medan Estate Village, Percut Sei Tuan Subdistrict, Deli Serdang Regency. Research Method: This study employs a quantitative research design, specifically an experimental study using a quasi-experimental approach. The research design utilized is a pretest-posttest with a control group. The sampling technique used was purposive sampling. The sample consisted of 24 respondents, with 12 respondents in each group. SSBM and foot massage therapy were administered for 2–3 consecutive days, each session lasting 10 minutes. Conclusion: Data analysis in this study utilized the Paired Sample t-test and the Wilcoxon Signed-Rank Test with α ≤ 0.05. The results of this study, using the Wilcoxon Signed-Rank Test, indicate that there is a significant effect of SSBM therapy and foot massage on blood pressure reduction in the elderly, with a p-value of 0.020.